Vertical Distribution of Arthropod Assemblages and the Effects of Weather Conditions on Arthropod Rain in a Temperate Conifer Forest - Yoshida, Tomohiro; Kusunoki, Yasunori; Fukano, Yuya; Hijii, Naoki (Frontiers in Forests and Global Change, 2021)
Vertical stratification of forests results in the occurrence of different arthropod assemblages between the vertical layers. Fallen arthropods from the canopy layers (i.e., “arthropod rain”) are additional food sources for predators thriving on the forest floor. However, the abundances of arthropods are strongly affected by weather conditions and vertical stratification. Therefore, in this study, we investigated the vertical distribution of arthropod assemblages and effects of temperature and precipitation on the arthropod rain in a temperate conifer (Cryptomeria japonica) forest. Arthropods were collected by water-pan traps and trunk-sticky traps in the upper canopy (16 m), lower canopy (10 m), and forest floor (0.5 m). Among the fallen arthropods collected by water-pan traps, wandering detritivores and herbivores were more abundant ranging from the forest floor to the upper canopy, whereas the abundance of wandering predators (mainly spiders) was similar in upper and lower canopies. However, detritivores, herbivores, and predators showed the highest abundance in the upper canopy among the flying arthropods. Wandering arthropods moved upwards from the forest floor toward the tree trunks more frequently than downwards, indicating the importance of arthropod immigration from the ground to arboreal habitats. Temperature and precipitation had different effects on fallen and moving arthropods among different taxonomic groups. Flying arthropods were affected only by temperature, while wandering detritivores and herbivores were affected by precipitation and temperature. Thus, the abundance of wandering and flying arthropods differed among the vertical layers of a temperate conifer forest; additionally, arthropod rain was closely associated with weather conditions.